WHAT IS A COMPREHENSIVE THEORY OF LAW? - Qurbonov Doniyorbek Davlat o'g'li (Journals Park Publishing, 2024)
This article reflects on the importance of philosophy to legal theorists. It is also taught that the law is a rational, legitimate regulator of the use of coercion and violence, and that it is a completely unreasonable regulator of the behavior of both individuals and authorities.
Keywords: Comprehensive theory, law, philosophical theory, violence, legal theories.